Disaster management and development in Bangladesh: education perspective - Rahman, Mohammad Aminur; Mallick, Fuad Hassan (© 2009 Published by Research Publishing Services., 2016)
This article was published in the Asian Journal of Environment and Disaster Management (AJEDM) [©2009 Published by Research Publishing Services] and the definite version is available at: http:// doi: 10.3850/S179392402009000052 The article website is at: http://rpsonline.com.sg/journals/101-ajedm/2009/0101/S179392402009000052.php